Scaling rainwater harvesting for irrigation in Kenya: potential sustainability risks and the need for adaptive governance - Radhika Singh; Nicholas Oguge; Collins Odote (Environmental Research: Food Systems)
Rainwater harvesting for irrigation (RWHI) systems offer many benefits to smallholder farmers in Kenya, including the possibility of agricultural intensification and improved resilience to climate change in more arid areas. However, the scaling of RWHI systems could inadvertently pose risks to environmental, social, and economic sustainability. Governance institutions in Kenya tasked with managing RWHI adoption processes are often unaware of such risks and ill-equipped to manage them when they emerge. To address this gap, this article first presents key insights from the literature on innovation scaling and adaptive governance on how undesirable effects of scaling can be mitigated. Then, based on the results of a global literature review and a case study in Kenya, it outlines potential environmental, social, and economic risks of scaling RWHI that may manifest in the Kenyan context. Environmentally, the biggest risk is that widespread adoption of RWHI, while increasing water availability at the household level, will alter hydrological flows and impact ecosystem functioning. Socially, major risks of scaling RWHI include increased inequities in water access and rights, as those with the resources to adopt RWHI are able to store and use more water than others. Finally, economic risks may emerge when farmers who have adopted RWHI to grow cash crops experience heightened vulnerability to market fluctuations. The article ends with a discussion on governance approaches that could be applied to ensure responsible RWHI scaling in Kenya. Key recommendations include creating institutions that embed adaptive governance mechanisms, democratizing the development of scaling strategies to ensure their collective ownership, and enhancing monitoring and data collection capacities for effective response. These measures aim to balance short-, medium-, and long-term objectives across various scales and user groups to maximize sustainability outcomes during RWHI scaling processes.